Autismo en los niños y su influencia en el aprendizaje de la Educación Inicial Jardinerito de la ciudad de Babahoyo, Provincia de Los Ríos - Dahik Mora, Erika Raquel (2019)
The present research work refers to autism in children and its influence on the learning of initial education Jardineritos of the city of Babahoyo, In the school education different children enter day by day who in turn have a different disability or a disorder that The teacher will investigate the strategic resources for the integral development of children, it is very important that in the family the processes of socialization and communication are carried out, learn to know their children to observe them in their childhood stage because sometimes they do not reach the skills needed to develop their skills, considering that there are internal and external factors that hinder the process in the child's adaptation, therefore the research project uses descriptive and field research types, analyze everything about autism and child learning, obtaining application data to eleven teachers and eighty-four Tro parents taking into account the personalities and different rhythms of learning found in the classroom, that is why the proposal arises to develop a teaching guide for teachers with recreational strategies, through exercises and activities that favor the cognitive area , social and motor. With the objective that four-year-old children achieve their skills through the development of skills